Criminology for the police - Paterson, Craig (Routledge advances in police practice and knowledge, 2022)
A criminology for the police? -- Disciplinary criminology and the police -- Criminology for the police -- Policing strategies -- From police culture to policing vulnerability -- Problem-solving for police officers -- The evolution of evidence-based policing -- Doing research on crime and policing -- Doing your own research.